2015
DOI: 10.1016/j.brachy.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

From whole gland to hemigland to ultra-focal high-dose-rate prostate brachytherapy: A dosimetric analysis

Abstract: PURPOSE: To assess the magnitude of dosimetric reductions of a focal and ultra-focal high-doserate (HDR) prostate brachytherapy treatment strategy relative to standard whole gland (WG) treatment. METHODS AND MATERIALS: HDR brachytherapy plans for five patients treated with WG HDR monotherapy were optimized to assess different treatment strategies. Plans were generated to treat the hemigland (HG), one-third gland (1/3G), and one-sixth gland (1/6G), as well as to assess treating the WG with a boost to one of tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Banerjee et al [28] have shown that a significant reduction in dosage to the organs at risk (OARs) was achieved using high-dose-rate focal brachytherapy, compared to whole gland and hemi-gland treatment. However, none of the previous studies on prostate cancer focal therapy included radiomics based detection of cancer lesions for therapy planning.…”
Section: Introductionmentioning
confidence: 99%
“…Banerjee et al [28] have shown that a significant reduction in dosage to the organs at risk (OARs) was achieved using high-dose-rate focal brachytherapy, compared to whole gland and hemi-gland treatment. However, none of the previous studies on prostate cancer focal therapy included radiomics based detection of cancer lesions for therapy planning.…”
Section: Introductionmentioning
confidence: 99%
“…The incidences of these toxicities with HDR as a boost to EBRT are w5.2%-12.7%, 17%-38%, 21%-26% 68,126 and 20%-50%, respectively. 127,128 Although new or worsening sexual dysfunction is very common after prostate BT, no consistent patterns have emerged demonstrating what structures might be spared to ameliorate this effect.…”
Section: Oculocutaneous Diseasementioning
confidence: 99%
“…126,129 Lower urinary tract symptoms share a positive association with bladder D 1cc , 130,131 with similar findings for rectal toxicities and hotspots. 127 IMBT studies have therefore focused on decreasing the dose to OARs, especially the urethra and periapical urethra, instead of increasing the prescription dose, given the relatively good prognosis for patients receiving standard doses.…”
Section: Oculocutaneous Diseasementioning
confidence: 99%
“…According to the recent reports, the incidence of grade ≥ 2 genitourinary toxicity after HDR brachytherapy for prostate cancer is around 9-10% [ 3 , 10 ], and reaches 12-19% in some publications [ 12 , 13 ]. Therefore, in patients with low risk localized (stage T1-T2a) PCa, the research have been directed toward different methods of focal prostate brachytherapy, which can varied from hemigland irradiation to focal therapy directly to the tumor foci [ 11 , 14 ]. Considering the high incidence of multifocal pattern of prostate involvement, in our Institute we abounded classic focal HDR brachytherapy for patients with PCa.…”
Section: Purposementioning
confidence: 99%